Antibacterial FormulationEmulgel Preparation Containing 3% Citronella Oil (Cymbopogon Nardus L) With Carbomer 0.5%, 1%, 1.5% - Devita Riafinola Andaririt (Strada Journal of Pharmacy, 2023)
Acne is a bacterial infection that can diminish a person's confidence. Acne is caused by the microorganisms Propionibacterium acnes. Citronella oil has citronellal, citronellol, geraniol compounds that contain a very strong antimicrobial activity. Therefore, emulsion-based topical preparations are made with carbomer bases that are suitable for use. This study sought to determine the effect of 0.5%, 1%, and 1.5% carbomer bases with 3% citronella oil extract on the chemical physics properties of emulsion preparations. (Organoleptic, pH, viscosity and dispersion, stability and Freeze-Thaw test). This investigation employed an experimental method to compare three formulas with varying levels of carbomer in an emulsion preparation test for citronella oil extract. The researcher then analysed the chemical substance's physical characteristics. Based on the evaluation results, it was determined that all formulations had identical organoleptic properties, including a silky texture, citronella oil aroma, and a white hue. According to the results of One-Way ANOVA, viscosity, pH, dispersion, stability, and the Freeze-Thaw test, there were no significant variations in the formula.